Real-time and non-invasive monitoring of embryonic stem cell survival during the development of embryoid bodies with smart nanosensor - Fu, Jiayin (2017)
Embryonic stem cells (ESCs)-derived embryoid body (EB) is a powerful model for the study of early embryonic development and the discovery of therapeutics for tissue regeneration. This article reports a smart nanosensor platform for labeling and tracking the survival and distribution of ESCs during the EB development in a real-time and non-invasive way. Compared with the cell tracker (i.e. DiO) and the green fluorescent protein (GFP), nanosensors provide the homogenous and highly-efficient ESC labeling. Following the internalization, intracellular nanosensors gradually release the non-fluorescent molecules that become fluorescent only in viable cells. This allows a continuous monitoring of ESC survival and distribution during the process of EB formation. Finally, we confirm that nanosensor labeling does not cause the significant influences to biological properties of the ESCs and EBs.